2005
DOI: 10.1167/iovs.04-1120
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Induces Thioredoxin through the Antioxidant-Responsive Element and Attenuates Retinal Light Damage in Mice

Abstract: SF induced Trx in murine retina and effectively reduced retinal light damage. Evidence suggests that the ARE is involved in the mechanism of Trx induction by SF in RPE cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
130
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 43 publications
4
130
0
1
Order By: Relevance
“…SF protects immature hippocampal neurons against death caused by exposure to hemin or to oxygen and glucose-deprivation (25). SF induces thioredoxin expression and attenuates retinal light damage in mice (26). It also has been reported that SF protects against 6-OHDA-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 96%
“…SF protects immature hippocampal neurons against death caused by exposure to hemin or to oxygen and glucose-deprivation (25). SF induces thioredoxin expression and attenuates retinal light damage in mice (26). It also has been reported that SF protects against 6-OHDA-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 96%
“…SF protects immature hippocampal neurons against death caused by exposure to hemin or to oxygen and glucosedeprivation (24). SF has been shown to induce thioredoxin expression and attenuates retinal light damage in mice (25). It has also been reported that SF may serve as a potential candidate for the treatment and/or prevention of PD.…”
Section: Discussionmentioning
confidence: 99%
“…RPE cell death plays a major role in the pathogenesis of age-related macular degeneration, the leading cause of blindness in the population Ͼ60 years of age in the developed world (2). Possible reasons given for the degeneration of RPE cells are their exposure to high oxidative stress and damaging irradiation (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%